Rancang Bangun Sistem Informasi E-Arsip Berbasis Web Menggunakan Subject Filing System Pada DINNAKERIND Demak - Evi Yuli Yanti; Yani Prihati; Satrio Agung Prakoso (INTECOMS: Journal of Information Technology and Computer Science, 2024)
This research aims to design a web-based e-archive information system using the subject-filing system method at DINNAKERIND Demak. The subject filing system method was chosen because of its ability to organize documents based on certain subjects or topics, facilitating more efficient access and search for archives. The research results are expected to provide insight into the effectiveness of web-based e-archive information systems with the application of the subject filing system in improving archive management in the DINNAKERIND Demak environment and using SDLC waterfall as the development method. The system created was also tested using black box testing and usability testing by 22 respondents, resulting in an overall score of 86.8%. With this system, it is hoped that it can help archive processing at DINNAKERIND, Demak district.